Stereoselective strategies to access spirotetronate natural products - Brion, Aurélien; Neuville, Luc; Masson, Géraldine (Comptes Rendus. Chimie)
Spirotetronates constitute a large family of natural products that have attracted significant attention due to their intriguing structures and broad biological activities. These compounds share a common spirocyclic 4-hydroxy-1-oxaspiro[4.5]deca-3,7-dien-2-one unit, whose synthesis has been actively pursued by chemists. In this review, we highlight various approaches to accessing diversely substituted spirotetronates, including methods that enable the total synthesis of selected natural targets. The Diels–Alder/Dieckmann route originally reported has been extensively developed and encompasses various diastereoselective processes. Although enantioselective transformations have been reported, they remain scarce. Additionally, although less explored, alkylation of ketones has been employed for the synthesis of alkoxyfuran-2(5H)-one scaffolds, and selected ring-forming strategies have been investigated to construct pre-functionalized cyclohexyl backbones.